Customer Journey Mediates the Role Of 4C Marketing Mix 4.0 on Customer Loyalty with User İnterface Moderation - Surya Bintarti; Adam Ariansyah Pirdaus (APMBA (Asia Pacific Management and Business Application), 2024)
Digitization in Indonesia has been on the rise since the Covid-19 pandemic, reshaping the lifestyle of the population with a shift from conventional to online shopping. E-commerce transactions, especially through smartphones, offer speed and convenience, making e-commerce the primary intermediary between businesses and consumers. For instance, Traveloka, despite the tourism industry's impact in 2021, remains a key developer, facing the staycation trend for continued transaction growth amid competition. Established in 2012, Traveloka Holding Ltd has successfully secured the top position in the Top Brand Awards. This study, conducted with 111 respondents in the Bekasi Regency, one of the largest metropolis city in the Indonesian capital region, aims to examine the impact of Traveloka's co-creation, currency, communal activation, and conversation on customer loyalty. Customer journey serves as a mediator, while the user interface does not significantly moderate the relationship. The results indicate that each element of the 4C Mix Marketing 4.0 directly contributes to enhancing user loyalty to Traveloka, although the mediating role of the customer journey tends to be low.